Global Oil Market and the U.S. Stock Returns - Maryam Ahmad; Matteo Manera; Mehdi Sadeghzadeh (Fondazione Eni Enrico Mattei (FEEM), 2015)
This paper provides an analysis of the link between the oil market and the U.S. stock market returns at the aggregate as well as industry levels. We empirically model oil price changes as driven by speculative demand shocks along with consumption demand and supply shocks in the oil market. We also take into account in our model all the factors that affect stock market price movements over and above the oil market, in order to quantify the pure effect of oil price shocks on returns. The results show that stock returns respond to oil price shocks differently, depending on the causes behind the shocks. Impulse response analysis suggests that consumption demand shocks are the most relevant drivers of the stock market return, relative to other oil market driven shocks. Industry level analysis is performed to control for the heterogeneity of the responses of returns to oil price changes. The results show that both cost side and demand side effects of oil price shocks matter for the responses of industries to oil price shocks. However, the main driver of the variation in industries' returns is the shock to aggregate stock market.
Keywords: G1; G12; Q41; 330; Oil Market; Oil Price; Stock Market